2011
DOI: 10.1007/s10452-011-9378-4
|View full text |Cite
|
Sign up to set email alerts
|

Portage connectivity does not predict establishment success of canoe-mediated dispersal for crustacean zooplankton

Abstract: Although community structure may be largely determined by local abiotic and biotic conditions under moderate levels of dispersal, anthropogenic activities can enhance dispersal rates far beyond what would otherwise occur in natural systems. We investigated the potential impact of recreational canoeing on crustacean zooplankton community structure in Killarney Provincial Park, Canada, where canoes that are transported between lakes via portage routes may enhance zooplankton community connectivity by providing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 69 publications
1
6
0
Order By: Relevance
“…This coupled with the low frequency with which anglers and canoeists clean and dry their equipment suggests that these groups may have the potential to act as vectors for their spread. The results are in accord with studies in North America which showed that anglers and boaters were travelling hundreds of kilometres between sites [31] , [32] and were frequently transporting muddy waders [31] , and the remnants of invasive aquatic plants on their boats [33] , [34] . Within this research, we investigated the movement patterns of anglers and canoeists to evaluate the biosecurity risk that they would pose should they become contaminated with INNS or pathogens.…”
Section: Discussionsupporting
confidence: 89%
“…This coupled with the low frequency with which anglers and canoeists clean and dry their equipment suggests that these groups may have the potential to act as vectors for their spread. The results are in accord with studies in North America which showed that anglers and boaters were travelling hundreds of kilometres between sites [31] , [32] and were frequently transporting muddy waders [31] , and the remnants of invasive aquatic plants on their boats [33] , [34] . Within this research, we investigated the movement patterns of anglers and canoeists to evaluate the biosecurity risk that they would pose should they become contaminated with INNS or pathogens.…”
Section: Discussionsupporting
confidence: 89%
“…For instance, we assumed that canals were the major zooplankton dispersal pathway; however, other dispersal vectors, such as waterfowl or boaters, may be important in moving organisms between waterbodies (Havel & Shurin ; Stasko et al . ). We found no significant influence of boat ramps on communities inside the CBP; additionally, Gray & Arnott () demonstrated that the egg bank and stream connections were the largest contributors of individuals to a lake, which suggests that canals likely outweigh other pathways of dispersal.…”
Section: Discussionmentioning
confidence: 97%
“…First, as younger anglers' participation in fishing increases, mobile platforms offer management agencies an opportunity to outreach and learn more about these demographics, as these are also less likely to engage with mail-in or inperson surveys (Fisher 1996;Recreational Boating and Fishing Foundation Outdoor Foundation 2018;Gundeland et al 2020). Second, mobile-based data provide information about the movement of a largely unknown group of anglers accessing waterbodies using non-motorised recreational boats, such as canoes and kayaks and who are similarly dispersal vectors for aquatic invasive species (Stasko et al 2012;Anderson et al 2014), but are not subject to conventional creel surveys conducted at boat launches. In summary, while prior work has demonstrated that actively collected mobile data (i.e.…”
Section: Discussionmentioning
confidence: 99%